Analysis of RNA expression by blood mononuclear cells stimulated by human rabies CSF - Willoughby, R. E.; Jia, S.; Hessner, M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In the absence of effective antivirals, survival from rabies has been correlated with the appearance of neutralizing antibody within 7 days of hospitalization. This adaptive humoral response follows the earlier innate immune response to rabies, which can be subverted by the rabies virus phosphoprotein. Understanding the cerebrospinal fluid (CSF) environment affecting innate and adaptive immunity to rabies virus is key to improving rabies survival. To sensitively detect the presence of cytokines, chemokines and other important immune modulators (small nucleotides and lipids) in CSF, we employed a novel bioassay whereby a well-controlled peripheral blood mononuclear cell (PBMC) population of a healthy blood donor is used asa sensitive biosensor that transcriptionally responds to these dilute disease-associated factors. The readout is a comprehensive genome-scale array. We examined 7 control CSF and 13 CSF samples from 6 patients with laboratory-confirmed rabies, dating from hospital days 4 to 26. Dog and bat rabies were equally represented. CSF was incubated with reporter (PBMC) for 9 hours, total RNA from PBMC was then extracted, labeled and analyzed using Affymetrix Human Genome U133Plus2.0 array. Unsupervised analysis separated rabies CSF from controls but did not clearly group rabies samples by patient, suggesting that rabies disease itself and associated medical treatments are greater determinants of the innate immune response to rabies measured in CSF than are intrinsic host variables. In general, interferon-induced genes were up-regulated while cytokine genes were downregulated in human PBMC responding to human rabies.